Impact of Mindful Leadership on Deviant Innovation Behavior among Post-90s Employees: Evidence from Chinese Enterprises - He, Junbo; Chen, chun-shuo (Environment and Social Psychology, 2025)
This paper explores how mindful leadership affects deviant innovation behavior among post-1990s born employees, which is a generation that is still emerging in the Chinese companies as the workforce. Based on the social exchange theory and mindfulness theory, the study examines the influence of mindfulness qualities of leaders on the motivation and the desire to engage in innovative behaviors that do not align with the norms of traditional norms but contribute positively to the growth of organizations. A quantitative survey used was carried out on 472 workers of various industries in China with the help of validated scales of measurement of mindful leadership, psychological safety, intrinsic motivation and deviant innovation. The data were evaluated using regression models, mediation tests using correlation analysis and regression models. Findings point out that mindful leadership contributes greatly to the deviant innovation behavior among the employees by increasing their psychological safety and intrinsic motivation. These variables were also found to mediate the relationship between mindful leadership and deviant innovation, which in turn confirms that mindful leadership has both direct and indirect consequences. The paper emphasizes that managers need to incorporate mindfulness training into their leadership training programs and organizational culture to elicit nontraditional but beneficial innovation behaviors among young workers. The results have an implication on the field of leadership theory and management of innovation as it helps to broaden the scope of mindfulness use in the study of organizational behavior.